Are you Wo(man) enough to get married? - Allagan, Tiurma M. P. (Indonesia Law Review, 2016)
The Indonesian Marriage Law states that marriage is a physical and spiritual relationship between a man and a woman as husband and wife in order to create an eternal happy family based on the Almighty God. This definition reflects that marriages in Indonesia must be between heterosexual couples. However, a question appears as to whether a man or a woman mentioned thereof includes a man and a woman who were hermaphrodite, intersex, or nowadays known as a person with Disorder of Sexual Development (DSD)? The case of AH whereby his marriage was cancelled by the Supreme Court in 2014 for since he was not considered as a man, confirms that this question is important to value the capacity of a person to marry. This writing will apply normative research as well as literature research methods upon the positive rules and regulations. The decisions of district courts upon the revision or change of gender and its legal basis will be analyzed and be the topic of discussion. The comparison will then be applied to compare the marriage requirements between Indonesian Law, Singaporean Law and Hong Kongese Law. The results of analysis and discussion will be the closure of the writing, as conclusions and advice, if any.